THE ROLE AND SIGNIFICANCE OF CHEMICAL DISCIPLINES IN THE TRAINING OF PHARMACISTS - I. Ukleina; R. Petinov (Вестник Северо-Кавказского федерального университета, 2022)
The high importance of high-quality training of specialists in the field of pharmacy for the protection of the health of Russian citizens is shown. The purpose of the research is to determine the role of chemical disciplines and the importance of pharmaceutical chemistry in the training of specialists in the pharmaceutical industry. The author characterizes the composition and complexity of mastering the chemical block of disciplines at the leading University of the North Caucasus Federal University. The interrelation of chemical disciplines and the need for a systematic approach to their study is substantiated. It is concluded that an important component of the pharmacist's competence model is chemical competence formed on the basis of an integrative approach.